Natriuretic peptide-directed medical therapy: a systematic review - Christella S. Alphonsus; Pooveshnie Govender; Reitze N. Rodseth; Bruce M. Biccard (Perioperative Medicine, 2020)
Abstract Natriuretic peptides (NP) are strongly associated with perioperative cardiovascular events. However, in patients with raised NP, it remains unknown whether treatment to reduce NP levels prior to surgery results in better perioperative outcomes. In this systematic review and meta-analysis, we investigate NP-directed medical therapy in non-surgical patients to provide guidance for NP-directed medical therapy in surgical patients. The protocol was registered with PROSPERO (CRD42017051468). The database search included MEDLINE (PubMed), CINAHL (EBSCO host), EMBASE (EBSCO host), ProQuest, Web of Science, and Cochrane database. The primary outcome was to determine whether NP-directed medical therapy is effective in reducing NP levels within 6 months, compared to standard of care. The secondary outcome was to determine whether reducing NP levels is associated with decreased mortality. Full texts of 18 trials were reviewed. NP-directed medical therapy showed no significant difference compared to standard care in decreasing NP levels (standardized mean difference − 0.04 (− 0.16, 0.07)), but was associated with a 6-month (relative risk (RR) 0.82 (95% confidence interval (CI) 0.68–0.99)) reduction in mortality.